Optimal configuration and sizing of regional energy service company's energy hub with integrated demand response. Issue 3 (18th November 2018) - Qiu, Zhi; Wang, Beibei; Huang, Junhui; Xie, Zhenjian
Abstract : The growing development of interactive energy systems has motivated a regional energy service company (ESCO) to build energy hubs (EH) that play a substantial role in the coupling of various energy carriers. EH configuration optimization is critical to the economic operation of an ESCO. Therefore, this study proposes a configuration and sizing model that considers the integrated demand response (IDR) to optimize the size of the infrastructures in an EH, and hence minimize the total cost. The EH, which is composed of converters and storage units, is modelled in the matrix form, wherein the operation constraints are expressed in detail. Subsequently, an IDR program based on both responsive thermal and electrical loads is innovatively incorporated into the optimization model, and its effects on EH planning were investigated. By considering several cases: (i) we confirm the effectiveness of the IDR in terms of both cost and capacity reduction on components in the EH; (ii) we show the limited impact of the IDR on the investment cost and equipment configuration, primarily owing to constraints on the maximal total number of dispatching hours; (iii) we observe variations in the impact degree on infrastructure capacity, based on several factors including load characteristics and the electricity–gas price ratio. © 2018 Institute of Electrical Engineers of Japan. Published by John Wiley & Sons, Inc.